Interest rate policy and the price puzzle in a quantitative business cycle model - Andreas Schabert (Institute for Advanced Studies (IHS), 2001)
In the empirical literature, monetary policy shocks are commonly measured as an innovation to a short-term nominal interest rate. In contrast, the majority of monetary business cycle models treats a broad monetary aggregate as the central bank's policy measure. We try overcome this disparity and present a business cycle model which allows to examine the effects of innovations to a non-contingent nominal interest rate rule. To obtain unique rational expectations equilibria we assume that changes in money supply are brought about open market operations. In addition to working capital, we consider staggered prices which enables real marginal costs to vary. Consistent with the empirical findings of Barth and Ramey (2000), the model predicts that real marginal cost and inflation rise in response to positive interest rate innovations. The mechanism corresponds to their 'Cost Channel of Monetary Transmission' and replicates typical monetary VAR results, including the puzzling behavior of prices.
Keywords: E5; E3; E63; 330; monetary transmission; interest rate shocks; open market operations; price puzzle; Zinspolitik; Schock; Preisrigidität; Transmissionsmechanismus; Kapitalkosten; Neukeynesianische Makroökonomik; VAR-Modell; Offenmarktpolitik; Theorie